Accompagner à la littéracie universitaire par le dialogue - Claire Polo (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The CLEFS program, which has been implemented in November 2018, in Lyon, supports students with special needs in their first year at university, to prevent them from dropping out. Dramatical means invested in this program make it possible to provide students with intense support: groups of maximum 12 people, tutoring, tripled time for transversal teaching on university methodology and literacy, critical and scientific thinking. A collaborative project-based approach enables us to address such skills in a real life perspective, aiming at organizing a final public event on the interdisciplinary issue studied. In this context, we intend to support their academic literacy through pedagogical tools fostering students’ autonomy, with a special focus on making sense of the use or production of written materials. Dialogue plays a great role in this meaning making process, since learning and reasoning may only occur in interaction with peers, with the didactical objects studied, with existing literature, and with the audience to whom the project is directed.